Implementing Trauma-Informed Practice into My Leadership - Nowaczyk, Stephanie (Journal of Practical Nurse Education and Practice, 2025)
This research explores strategies for implementing a trauma-informed approach as a leader and nurse educator, addressing the question: How can I integrate trauma-informed practice (TIP) into my leadership? Using a first-person, action-orientated approach that included a one-hour semi-structured interview with a subject-matter expert (SME), completing bi-weekly journaling, and meeting twice with feedback partners (FPs) to ensure rigour within the data collection. An extensive literature review focused on defining trauma and exploring TIP practices. Two rounds of data collection and thematic analysis revealed three key components of trauma-informed leadership: awareness, connection, and a psychologically safe environment. The goal was to understand how as a leader I could implement TIP to support individuals who have experienced trauma. Recommendations include promoting educational opportunities and providing tools for trauma-informed leaders. Implementing TIP has enabled me to create a supportive, healing environment within my leadership and organization, connecting individuals to community resources and fostering positive change.